(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the postoperative survival outcomes of patients undergoing laparoscopic gastrectomy for gastric cancer using the Kaplan–Meier method at 115 People’s Hospital. Subjects and Methods: This was a retrospective, descriptive case series study. All patients who underwent laparoscopic gastrectomy for gastric cancer at the Department of General Surgery, 115 People’s Hospital, from January 2020 to December 2024, were included Clinical data were collected from medical records. Overall survival (OS) and disease-free survival (DFS) were analyzed using the Kaplan–Meier method. Results: A total of 144 patients underwent laparoscopic gastrectomy with D2 lymph node dissection for gastric cancer. The recurrence rate was 4.9%. The distant metastasis rate was 21.5%, including: 17 cases of peritoneal metastasis, 7 cases of hepatic metastasis, 2 cases of pulmonary metastasis, 1 case of distant lymph node metastasis, and 4 cases with multiple-organ metastases. According to Kaplan–Meier survival estimates, the mean overall survival (OS) was 60.1 months (95% confidence interval [CI]: 55.5–64.7 months). The mean disease-free survival (DFS) was 55.4 months (95% CI: 49.6–61.1 months). The 1-year and 3-year overall survival rates were 96% and 86%, respectively. The 1-year and 3-year disease-free survival rates were 90% and 80%, respectively. Postoperative survival time decreased progressively with higher tumor stage.